2016
DOI: 10.3233/rnn-160661
|View full text |Cite
|
Sign up to set email alerts
|

Inosine enhances recovery of grasp following cortical injury to the primary motor cortex of the rhesus monkey

Abstract: These findings demonstrate that inosine can enhance recovery of function following cortical injury in monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 118 publications
1
14
0
Order By: Relevance
“…Consistent with these results, previous studies have reported the involvement of cerebral cortex lesions in the functional recovery of manual dexterity [ 27 ]. The impaired movement of the affected hand and the relative increase in reaction time in stroke patients have been reported to be correlated with the size of the brain lesions in the ipsilateral hemisphere [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with these results, previous studies have reported the involvement of cerebral cortex lesions in the functional recovery of manual dexterity [ 27 ]. The impaired movement of the affected hand and the relative increase in reaction time in stroke patients have been reported to be correlated with the size of the brain lesions in the ipsilateral hemisphere [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…The HDT was used to evaluate fine motor functions of the hand and digits, as described in previous rhesus monkey studies by Moore et al [ 27 ]. The HDT used in this study was slightly modified, whereby the testing apparatus was designed for a cage-based training system.…”
Section: Methodsmentioning
confidence: 99%
“…Under physiologic conditions, blood levels of inosine are increased by exercise and ingestion of certain foods (organ meats, beer, spinach) and exhibit diurnal variations. Over the past two decades, inosine has been shown to evoke significant improvements in motor function and visceral organ control in preclinical models of neurologic injury including SCI [19][20][21][22][23][24], stroke [25][26][27][28][29], traumatic brain injury [30], multiple sclerosis (MS) [31][32][33][34][35] and Parkinson's disease (PD) [36] through its ability to enhance the growth of axon collaterals from undamaged neurons. The basis of these beneficial effects stems from its antioxidant, anti-inflammatory, axogenic and neuroprotective properties (reviewed in [37]).…”
Section: Inosinementioning
confidence: 99%
“…The basis for this difference is likely in part a difference in the underlying biology between rodents and humans and suggests that the response to injury in the rodent may be different than that in the primate. Our NHP model of cortical injury is a well-controlled and minimally variable model that has been tested and validated in our laboratory and used to assess various therapeutic agents (Moore et al 2012;Moore et al 2013;Moore et al 2016). Results have consistently found that focal injury to the hand representation of motor cortex produces a well-characterized deficit in fine motor function, which is very similar to that seen in human stroke patients.…”
Section: Comparison With Similar Scalementioning
confidence: 85%